Mengatasi Kesepian: Program Psikoedukasi untuk Mahasiswa Rantau di Yogyakarta: Overcoming Loneliness: Psychoeducational Programs for Overseas Students in Yogyakarta - Chanaka, Jeveline; Haslinda, Waode Indah; Tangkilisan, Elya Nathany; Putri, Nur Amalia; Ginting, Della Geshi Br; Wulandari, Nanda Yunika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Loneliness is a psychological phenomenon commonly experienced by overseas students due to limited social support, cultural shocks, and challenges of adapting to a new environment. This program aims to increase international students' understanding and capacity to manage loneliness through a structured psychoeducational approach. This activity was attended by 15 overseas students aged 18-25 years old who live independently in Yogyakarta. The program is carried out in three stages, namely preparation (collection of needs data), implementation (interactive seminars, videos, and discussions), and evaluation (pre-test and post-test). The paired-samples t-test showed a significant increase in participants' understanding (p < 0.001) after psychoeducation. These findings show that psychoeducation programs are effective in improving overseas students' understanding of loneliness and adaptive coping strategies.